2016
DOI: 10.1016/j.mce.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as novel biomarkers for bone diseases – Complex signatures for multifactorial diseases?

Abstract: Biomarkers are essential tools in clinical research and practice. Useful biomarkers must combine good measurability, validated association with biological processes or outcomes, and should support clinical decision making if used in clinical practice. Several types of validated biomarkers have been reported in the context of bone diseases. However, because these biomarkers face certain limitations there is an interest in the identification of novel biomarkers for bone diseases, specifically in those that are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
141
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 128 publications
0
141
0
8
Order By: Relevance
“…When the participants were subdivided into long-lived and short-lived subgroups, a multiplex of aging biomarker with the expression of miR-211-5p, miR-374a-5p, miR-340-3p, miR-376c-3p, miR-5095, and miR-1225-3p was proposed to be significantly differentially expressed and correlated with lifespan, providing a basis for investigating miRNAs as potential longevity predictors and regulators of aging process [81]. Circulating miRNAs from blood samples have been also investigated as biomarkers of aging-associated diseases, like cardiovascular diseases, neurodegenerative diseases, type 2 diabetes mellitus, and bone diseases [78, 82, 83]. Body fluids other than blood samples are also a reservoir of miRNA biomarkers.…”
Section: Mirna Biomarkers Of Senescence and Agingmentioning
confidence: 99%
“…When the participants were subdivided into long-lived and short-lived subgroups, a multiplex of aging biomarker with the expression of miR-211-5p, miR-374a-5p, miR-340-3p, miR-376c-3p, miR-5095, and miR-1225-3p was proposed to be significantly differentially expressed and correlated with lifespan, providing a basis for investigating miRNAs as potential longevity predictors and regulators of aging process [81]. Circulating miRNAs from blood samples have been also investigated as biomarkers of aging-associated diseases, like cardiovascular diseases, neurodegenerative diseases, type 2 diabetes mellitus, and bone diseases [78, 82, 83]. Body fluids other than blood samples are also a reservoir of miRNA biomarkers.…”
Section: Mirna Biomarkers Of Senescence and Agingmentioning
confidence: 99%
“…By targeting the mRNAs of protein-coding genes, miRNAs play a critical role in a variety of biological and pathological processes [13][14][15][16]. As a result, using miRNAs as biomarkers have received widespread attention [17][18][19]. While most miRNAs are found intracellularly, a significant number have also been observed extracellularly in saliva, urine and breast milk [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups reported miRNAs circulated in highly stable, cell-free form in body fluids including serum and plasma4567. Because they met the three fundamental criteria of valuable biomarker: measurability, validation and utility, circulating miRNAs had great potential to serve as noninvasive biomarkers for molecular diagnostics89. Only recently, results from circulating miRNAs analysis in patients with osteopenia, osteoporosis and fragility fractures have been reported.…”
mentioning
confidence: 99%
“…Meanwhile, Panach et al identified three up-regulated miRNAs (miR-122-5p, miR-125b-5p and miR-21-5p) were valuable biomarkers for osteoporotic fracture14. Due to the diverse nature of study designs, the number and type of regulated miRNAs identified varies significantly9. Specific and sensitive circulating miRNA biomarkers for postmenopausal osteoporosis has not been fully established and their potential of functioning as biomarkers for mechanical unloading induced osteoporosis remain unclear.…”
mentioning
confidence: 99%